Developing Integrated Learning Based On Digital Literacy And Ethics In Indonesian Subjects - Wardani, Septiana Kusuma; Ardjaka , Sugiyono; Sapta , Andy (Jurnal Elementaria Edukasia, 2024)
The use of gadgets is a technological advance that has an impact on students' development. Excessive use of gadgets can have a negative impact on students. Blended learning models that integrate digital literacy and ethics provide guidance for students to use technology wisely. This study aims to develop and test an integrated learning model based on digital literacy and ethics in Indonesian language teaching. The research method uses research and development to develop and validate digital literacy and ethics products. The subjects were fifth graders from Srengat Primary School. Data analysis using descriptive statistics and percentages with Content Validity Ratio test for expert validation and paired t-test. The Content Validity Ratio results from four experts showed that integrated learning models were very important, with scores ranging from 0.0 to 1.0 and an overall average of 0.6. The average expert validation scores were 3.6, 3.8, 3.9 and 3.8, respectively, ensuring the validity of the e-book for digital literacy and ethics. Paired sample t-tests with values of t -13.27 and p-0.000 showed statistically significant improvements in understanding of digital literacy and ethics. In conclusion, digital literacy and ethics with e-book products effectively enhances students' skills in critical information evaluation and digital responsibility. Future studies are recommended to explore and refine curriculum design to promote positive digital character and develop students as critical readers and responsible digital users.